Application and Validation of an Ecological Quality Index, ISEP, in the Yellow Sea - Jae-Won Yoo; Yong-Woo Lee; Mi-Ra Park; Chang-Soo Kim; Sungtae Kim; Chae-Lin Lee; Su-Young Jeong; Dhongil Lim; Sung-Yong Oh (Journal of Marine Science and Engineering, 2022)
An ecological index of macrobenthic communities is an important tool for assessing the biological quality of habitats and ecosystems. We tested the performance of the inverse function of the Shannon–Wiener evenness proportion (ISEP) with data from the entire west coast of Korea, seasonally sampled from 2006 to 2008. Two validations were performed: (1) examination of the relationship between ISEP and environmental factors and (2) correspondence between the ISEP and the Pearson–Rosenberg (P-R) model for the species-abundance-biomass (SAB) patterns and taxonomical variations. The ISEP was significantly correlated with suspended solids but independent of other natural habitat conditions due to their low to moderate contamination levels. From this, ISEP performed as expected in transitional zones of low salinity and applications across habitats of various sediments. The SAB patterns and taxonomic variations along the ISEP grades showed marked similarities to the P-R model. The only departure was biomass, which increased after the normal status. The increase was interpreted as reflecting a healthier and more mature status. Taxonomic variation patterns and the taxa composition that characterized either poor or healthy status corresponded well with the P-R model. The conformity to the P-R model indicates the capability and potential applicability of the ISEP to other coastal systems.